2005
DOI: 10.1080/14992020500243893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cochlear implant simulation on immediate memory in normal-hearing adults

Abstract: This study assessed the effects of stimulus misidentification and memory processing errors on immediate memory span in 25 normal-hearing adults exposed to degraded auditory input simulating signals provided by a cochlear implant. The identification accuracy of degraded digits in isolation was measured before digit span testing. Forward and backward digit spans were shorter when digits were degraded than when they were normal. Participants' normal digit spans and their accuracy in identifying isolated digits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…A necessary next step to further validate our hypothesis (a shared cognitive resource affected by degradation and memory load alike) would be to explore cognitive capacities closer to their near maximum and test the influence of acoustic degradation accordingly. Only behavioral evidence pointing in this direction is available (Burkholder et al, 2005); the authors tested listeners' actual capacity limits (digit span) in vocoded speech and predicted this limit from the accuracy to identify the degraded single items. Our setup, instead, allows measuring the neural consequences of degraded (and potentially inaccurate) information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A necessary next step to further validate our hypothesis (a shared cognitive resource affected by degradation and memory load alike) would be to explore cognitive capacities closer to their near maximum and test the influence of acoustic degradation accordingly. Only behavioral evidence pointing in this direction is available (Burkholder et al, 2005); the authors tested listeners' actual capacity limits (digit span) in vocoded speech and predicted this limit from the accuracy to identify the degraded single items. Our setup, instead, allows measuring the neural consequences of degraded (and potentially inaccurate) information.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research as well as pilot digit recognition tests with naive participants, 4-band, 8-band, and 16-band versions were used in the final MEG study; of these conditions, 4-band speech was assumed to be most effortful to the perceptual-cognitive system, whereas correct identification of the digit (from this small set of 10 digits) from such degraded audio was still possible (see behavioral performance below). This is important because we did not aim at manipulating speech intelligibility per se but first and foremost aimed at manipulating the perceptual uncertainty and the concomitant effort evoked by degraded speech (Pisoni, 2000;Burkholder et al, 2005;Pichora-Fuller and Singh, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to separate the contributions of identification and recall errors on repetition errors have either utilized shadowing tasks (Rabbitt, 1991;Sarampalis et al, 2009), where each item is identified immediately after it is presented or "mathematically" compensated for identification errors (Dallett, 1964;Burkholder et al, 2005). Shadowing tasks either discard trials in which participants make identification errors (Rabbitt, 1991) or score participants based on the ability to recall and repeat what they identified (Sarampalis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most importantly for clinical applications is that shadowing tasks require more time to administer because participants must be given adequate time to repeat each item of the list. Dallett (1964) and Burkholder et al (2005) estimated the probability of correctly recalling a list of N items P(R | N) from a measure of the probability of correctly repeating a list of N items P(C | N) and the probability of correctly identifying isolated items P(I). The underlying assumptions used in their estimates are not clearly stated and appear unrealistic.…”
Section: Introductionmentioning
confidence: 99%